The differences between American and British English - Abdulhamzah Abdul.z, Ali (Technium Social Sciences Journal, 2025)
Any linguistic consideration of the differences between American and British English must focus on two points: (a) What are these differences? (b) Why do they exist? Although point (a) seems the more straightforward and methodologically achievable of these points, it is complicated by the fact that we lack certain historical data, particularly with respect to certain dialects; it is impossible to catalog undocumented differences, after all. Point (b) is also difficult to answer because of data gaps and methodological differences in evaluating the divergent evolution of English across the Atlantic. However, this paper presents an overview of the current state of linguistic scholarship on both points (a) and (b).